Incidence of Gestational Diabetes Mellitus in Pregnant women from Rural Background Attending Antenatal Care Clinic - Gupta, Kumud; Parmar, Meenal; Dubey, Smarika (International Journal of Medical Research and Review, 2015)
Objective: To assess the incidence of Gestational Diabetes Mellitus in pregnant women from rural background attending antenatal care clinic. Introduction: Gestational diabetes mellitus (GDM) is defined as any degree of glucose intolerance with onset or first recognition during pregnancy. Incidence of GDM is increasing worldwide for recent trends in obesity and advancing maternal age, with huge healthcare and economic costs. Depending on the population studied and the diagnostic test employed, prevalence may range from 2.4 to 21 per cent of all pregnancies. Method: 75 gm OGTT was performed on pregnant women attending antenatal clinic in NIMS Medical College and Hospital, Jaipur, Rajasthan, incidence then calculated. Result: Out of 511 patients studied, maximum percentage of patients with GDM (42.85%) were seen in age group of >/= 36 years, followed by 31-35 years (9.84%). Incidence of GDM in rural area of Jaipur in our study was 03.32%. Conclusion: Of total 511 patients 17 patients were diagnosed to have Gestational Diabetes Mellitus thus incidence came out to be 3.32%. Out of these 17 GDM patients, 3 (17.64%) patients were diagnosed in first trimester and thus diagnosing pregnant patients with high risk factors in first trimester, proved to be beneficial as early diagnosis and treatment reduces maternal and fetal complications. Association of presence of risk factors and GDM was not statistically significant and would have missed 13 (76.47%) patients.